TCMIO: A Comprehensive Database of Traditional Chinese Medicine on Immuno-Oncology - Liu, Zhihong; Cai, Chuipu; Du, Jiewen; Liu, Bingdong; Cui, Lu; Fan, Xiude; Wu, Qihui; Fang, Jiansong; Xie, Liwei (Frontiers in Pharmacology, 2020)
Advances from immuno-oncology (IO) make immunotherapy becoming a powerful tool for cancer treatment. With the discovery of increasing number of IO targets, many herbs or ingredients from traditional Chinese medicine (TCM) have shown immunomodulatory function and anti-tumor effects via targeting the immune system. However, the knowledge of underlying mechanisms is limited due to the complexity of TCM with multiple ingredients acting on multiple targets. To address this issue, we present TCMIO, a comprehensive database of Traditional Chinese Medicine on Immuno-Oncology, for exploring the molecular mechanisms of TCM in modulating cancer immune microenvironment. Over 120,000 small molecules against 400 IO targets were extracted from public database and literatures. Those ligands were further mapped to the chemical ingredients of TCM, identifying herbs that interacts with IO target. Furthermore, we applied network inference-based approach to identify the potential IO targets of natural products in TCM. All these data along with cheminformatics and bioinformatics tools were integrated into the publicly accessible database. Chemical structure mining tools are provided to explore the chemical ingredients and ligands against IO targets. The herb-ingredient-target network that could generate online and pathway enrichment analysis for TCM or prescription is available. This database is functional in structure mining the chemical ingredients and network analysis for TCM. We believe this database provides comprehensive resource for further research on the mechanism exploration of TCM in cancer immunity, and TCM-inspired identification of novel drug leads for cancer immunotherapy. TCMIO can be publicly accessed at http://tcmio.xielab.net.